INVENTARISASI JENIS-JENIS BAMBU YANG BERPOTENSI SEBAGAI OBAT DI KABUPATEN KARANGASEM BALI - Sujarwo, Wawan; Arinasa, Ida Bagus Ketut; Peneng, I Nyoman (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2010)
Bamboo occurs from lowland to highland. It is commonly utilized for construction, handicrafts and households, but its use as medicine is less known. This inventory revealed that there are six bamboo species that are potential to be used as medicine, i.e. bambu tali (Gigantochloa opus (J.A. & J.H. Schult.) Kurz), bambu ampel gading (Bambusa vulgaris Schrad. ex Wendl. var stricta), bambu pingit (Gigantochloa hasskarliana (Kurz) Backer ex Heyne), bambu tamblang gading (Schizostachyum brachycladum Kurz), bambu buluh lengis (Schizostachyum lima (Blanco) Merr.) and bambu petung (Dendrocalamus asper (Schult.) Backer ex Heyne). Further research is needed to determine the content of active compounds of those bamboo.